Characterization of Eu doped ZnO micropods prepared by chemical bath deposition on p-Si substrate. (April 2022) - Althumairi, Nouf Ahmed; Baig, Irshad; Kayed, Tarek Said; Mekki, Abdelkarim; Lusson, Alain; Sallet, Vincent; Majid, Abdul; Fouzri, Afif
Abstract: The chemical bath deposition method was used to synthesize Eu-doped ZnO on p-type (100) silicon. The SEM image shows the formation of micropod-like ZnO. EDX and XPS measurements showed an increase in the Eu concentration up to 2.54% and the simultaneous presence of Eu 3+ and Eu 2+ . XRD analysis confirmed that the interstitial Eu 3+ ions distorted the four tetrahedral bonds, and the substitution of Eu 2+ ions increased the c lattice parameter. Only Eu 3+ 5 D0 → 7 F2 transition-related emission was observed, so a weak transfer energy from the ZnO matrix to the Eu ion occurred. However, the competition between the emission of deep-level defects in the host matrix and that of Eu 3+ ions deforms the visible emission towards the red color. The I–V measurements of the Eu-ZnO/p-Si heterojunctions showed diode-like behavior with a low rectification ratio and a barrier height around 0.84 eV not affected by the Eu concentration. Highlights: Eu-doped ZnO micropods on p-type (100) substrate have been elaborated by chemical bath deposition (CBD) method. Simultaneous presence of Eu 3+ and Eu 2+ into ZnO matrix is confirmed by XPS. No efficient transfer energy from the ZnO matrix to Eu ion has been occurred. Eu doped ZnO micropods is a possible candidate for future orange emitting light sources. The barrier height of Eu-ZnO/p-Si heterojunctions is not affected by the variation of Eu concentration.